Role of Metformin Monotherapy Vs Metformin Plus Dapagliflozin in New Onset T2DM Among 40 Plus Obese Women in Glycaemic Control - Amarjeet Singh; Ashima Badyal; Suman Kotwal; Vishal R Tandon (Dr. Annil Mahajan, 2024)
Objective: A Randomized, open-label comparative clinical study was conducted to evaluate the comparative efficacy and safety of Metformin 500mg twice daily versus Metformin 500mg twice daily Plus Dapagliflozin (10mg) once daily in achieving glycemic control among new onset T2DM in forty plus obese women. Method: A total of 100 subjects were enrolled in the study and after inclusion exclusion criteria 60 subjects were randomized into two groups. Group A received Metformin 500mg twice daily and Group B received Metformin twice daily and Dapagliflozin 10 mg once daily. FBS and PPBS were done at Day 0, 4th week, 8th week, 12th week, HbA1c was done on 0 days and 12 weeks. Results: Metformin plus Dapagliflozin was found to be significantly superior at the 4th-week p value < 0.001 and remained comparable at the 8th and 12th weeks to Metformin alone on FBS and PPBS. The percentage reduction was clinically significant (>10%) reduction for the Metformin plus Dapagliflozin group when compared to the Metformin group (4.46%). Conclusion: Dapagliflozin in combination with Metformin had superior efficacy to Metformin alone in achieving tight glycemic control.